Ultrahigh sensitivity wearable sensors enabled by electrophoretic deposition of carbon nanostructured composites onto everyday fabrics. Issue 5 (20th January 2022) - Doshi, Sagar M.; Murray, Colleen; Chaudhari, Amit; Sung, Dae Han; Thostenson, Erik T.
Abstract : Functionalized carbon nanotubes are deposited using an aqueous electrophoretic deposition process on everyday fabrics to create flexible wearable sensors, with ultrahigh sensitivity to detect human movements, from arm flexing to finger bending. Abstract : Wearable sensors are of increasing interest in emerging applications such as human–computer interaction, electronic skin, smart robotics, and rehabilitation monitoring. Here we report a novel garment-based sensor by integrating nanocomposite coatings on commercially available fabrics. The sensing fabric is soft to the touch, breathable, and shows ultrahigh sensitivity of the electrical response to fabric deformation. A water-based electrophoretic deposition (EPD) technique at room temperature is used to deposit the nanocomposite films of polyethyleneimine (PEI) functionalized carbon nanotubes (CNT). The thin film nanocomposite creates an electrically conductive piezoresistive sensing network by uniformly coating the individual fibers within the fabric, and the coating is chemically bonded to the fiber surfaces. When integrated into garments, the sensors show remarkable sensitivity (∼3000% resistance change) to elbow/knee motion. In addition to large joint motion, the sensors are able to detect delicate motions, such as finger movement and muscle contraction. We demonstrate the ability to deposit CNT-PEI nanocomposite coatings on commercially available fabrics with different textile structures and natural/synthetic fibers such as wool, rayon, polyester, cotton and nylon. The industrial scalability of the EPD process, combined with the resulting textile sensors' extraordinary sensitivity, offers the potential to develop the next generation of wearable functional garments.